Financial stability considerations for monetary policy: Theoretical mechanisms - Andrea Ajello; Nina Boyarchenko; François Gourio; Andrea Tambalotti (Federal Reserve Bank of Chicago, 2022)
This paper reviews the theoretical literature at the intersection of macroeconomics and finance to draw lessons on the connection between vulnerabilities in the financial system and the macroeconomy, and on how monetary policy affects that connection. This literature finds that financial vulnerabilities are inherent to financial systems and tend to be procyclical. Moreover, financial vulnerabilities amplify the effects of adverse shocks to the economy, so that even a small shock to fundamentals or a small revision of beliefs can create a self-reinforcing feedback loop that impairs credit provision, lowers asset prices, and depresses economic activity and inflation. Finally, monetary policy may affect the buildup of vulnerabilities, but the sign of the impact along some of its transmission channels is theoretically ambiguous and may vary with the state of the economy.
Keywords: E32; E44; E58; G2; 330; monetary policy; financial stability; financial crises; credit; leverage; liquidity; asset prices